Bridging the gap: aligning physical work capacity testing with actual endurance performance in military settings - Jan Drozd; Jiří Neubauer; Jiří Sekanina; Marek Sedlačík (Frontiers in Psychology)
Physical fitness tests are essential for evaluating the endurance capabilities of military personnel. In many armed forces, including the Czech Republic’s, the Physical Working Capacity at a heart rate of 170 beats per minute (PWC 170) test is used to predict performance on the 12-min Cooper run, a widely accepted measure of endurance. However, concerns exist regarding the accuracy of the currently used conversion between PWC 170 test results, specifically W170/kg (watts per kilogram of body weight), and actual 12-min run performance. This study directly investigates the relationship between W170/kg and 12-min run times among military recruits and students (military personnel) from a university with a military program. Utilizing regression analysis, we found a significant positive correlation between W170/kg and 12-min run performance. However, the currently used conversion significantly underestimated actual 12-min run performance across all analyzed groups. These findings highlight a critical need to revise the existing conversion standard between W170/kg and 12-min run performance to ensure a more accurate and effective assessment of endurance capabilities in military personnel.